1967
DOI: 10.1113/expphysiol.1967.sp001936
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vasopressin, Theophylline and Cyclic 3'‐5'‐adenosine Monophosphate (Cyclic Amp) on Sodium Transport Across the Frog Skin

Abstract: The effects of vasopressin, theophylline and cyclic AMP on sodium transport across isolated frog skin have been studied using 24Na for the measurement of sodium fluxes. Both vasopressin and theophylline produced consistent increases in short-circuit current, sodium influx and efflux, with a reduction in partial resistance of the skin. The same results were obtained with cyclic AMP only when it was combined with small (loses of theophylline which were by themselves ineffective. The similarity of effect of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1968
1968
1992
1992

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…These results suggest stimulation ofNa' absorption by alveolar epithelium. Cyclic-AMP mediated stimulation of Na' absorption has also been observed in amphibian urinary bladder and amphibian skin (23)(24)(25). In these epithelia, antidiuretic hormone stimulation of electrogenic Na' absorption is mediated by an increase in cellular levels of cAMP.…”
Section: Resultsmentioning
confidence: 87%
“…These results suggest stimulation ofNa' absorption by alveolar epithelium. Cyclic-AMP mediated stimulation of Na' absorption has also been observed in amphibian urinary bladder and amphibian skin (23)(24)(25). In these epithelia, antidiuretic hormone stimulation of electrogenic Na' absorption is mediated by an increase in cellular levels of cAMP.…”
Section: Resultsmentioning
confidence: 87%
“…This action may be mediated by cyclic AMP (Orloff & Handler, 1962;Baba et al, 1967). The studies reported here show that amiloride may interact competitively with ADH and also with both dibutyryl cyclic AMP and theophylline.…”
Section: Discussionmentioning
confidence: 88%
“…Sodium ions now flow into the cells under a chemical gradient and a reduced electrical gradient. However, theophylline also increases sodium transport in short circuited skins (Baba et al 1967) where sodium ions can move independently of chloride ions. It is clear that separate channels for sodium and chloride ions must exist.…”
Section: Adh Action On Frog Skinmentioning
confidence: 99%
“…ADH increases sodium transport and water flow along an osmotic gradient in both of these tissues (Fuhrman & Ussing, 1951;Koefoed-Johnsen & Ussing, 1953;Bentley, 1966). ADH, the cyclic nucleotide and theophylline produce indistinguishable effects on sodium transport in the frog skin and toad bladder (Baba, Smith & Townshend, 1967;Orloff & Handler, 1961, 1964. It is considered that theophylline mimics ADH by preventing the intracellular break-down of cyclic 3',5'-AMP to 5'-AMP by phosphodiesterase (Butcher & Sutherland, 1962).…”
Section: Introductionmentioning
confidence: 99%